Exploring HOTS on global warming concepts, self-efficacy and learning motivation among high school students - Lina Aviyanti; Nuzulira Janeusse Fratiwi; Amalia Weka Gani; Abdul Salam; Gilbert Hugo T. Simbolon; Muhammad Guntur Purwanto (Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to explore Higher-Order Thinking Skills (HOTS) in relation to global warming materials, self-efficacy, and learning motivation among high school students. This study employed a quantitative descriptive method, involving 268 students (119 males and 149 females) from three high schools in West Java, Indonesia. The instruments used in this study included two-tier multiple-choice questions to measure higher-order thinking skills (HOTS), the Physics Learning Self-Efficacy (PLSE) scale to assess self-efficacy, and a Likert scale questionnaire to evaluate learning motivation. Findings revealed that students excelled in analyzing and evaluating tasks but struggled with tasks involving creation. Self-efficacy was moderate, with students showing confidence in their theoretical knowledge but less so in applying it to real-world situations. Learning motivation was generally high, particularly in terms of resilience and achievement, though persistence and engagement required improvement. However, the regression analysis indicated no significant relationship between self-efficacy and HOTS or between learning motivation and HOTS, reflecting that self-efficacy and learning motivation alone do not directly predict students' performance in HOTS. These results emphasize the need for educational strategies that promote HOTS, enhance self-efficacy, and sustain learning motivation to equip students for increasingly complex global challenges.